The Utility of the Family Empowerment Scale With Custodial Grandmothers - Hayslip, Bert (J Appl Gerontol, 2016)
The Family Empowerment Scale (FES) was developed specifically to assess empowerment in families with emotional disorders. Its relevance to custodial grandfamilies is reflected in the difficulties in grandchildren's social, emotional, and behavioral functioning, wherein such difficulties may be explained via either reactions to changes in their family structure or in their responses to the newly formed family unit. Utilizing 27 items derived from the 34-item version of the FES, which had represented differential levels of empowerment (family, service system, community) as indexed by one's attitudes, knowledge, and behavior, we explored the factor structure, internal consistency, construct, and convergent validity of the FES with grandparent caregivers. Three-hundred forty-three (M age = 58.45, SD = 8.22, n Caucasian = 152, n African American = 149, n Hispanic = 38) custodial grandmothers caring for grandchildren between ages 4 and 12 years completed the 27 FES items and various measures of their psychological well-being, grandchild psychological difficulties, emotional support, and parenting practices. Factor analysis revealed three factors that differed slightly from the originally proposed FES subscales: Parental Self-Efficacy/Self-Confidence, Service Activism, and Service Knowledge. Each of the factors was internally consistent, and derived factor scores were moderately interrelated, speaking to the question of convergent validity. The construct validity of these three factors was evidenced by meaningful patterns of statistically significant correlations with grandmothers’ psychological well-being, grandchild psychological difficulties, emotional support, and parenting practices. These factor scores were independent of grandmother age, health, and education. These findings suggest the newly identified FES factors to be valuable in understanding empowerment among grandmother caregivers.